Αξιολόγηση βιοδραστικότητας και έλεγχος αντιμικροβιακής δράσης αρωματικών και φαρμακευτικών φυτών της Κύπρου - Xαραλάμπους, Ζήνα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
The purpose of this study was to evaluate for first time the aromatic and medicinal plants of Cyprus flora, to the phytochemical composition, antioxidant capacity and antimicrobial properties of plants in the family Lamiaceae. Specifically, the five plants studied were: Thymus vulgaris (thyme), Satureja montana (savory), Origanum dubium (oregano), Sideritis spp. (Sideritis or mountain tea) and Salvia fruticosa (sage/). The identification and classification of phenolic compounds were done with photometric techniques and the antioxidant capacity was determined by the method of FRAP (Ferric Reducing Antioxidant Power). The antimicrobial activity of extracts was studied in two pathogens of plants (Clavibacter michiganensis subsp. michiganensis and Xanthomonas campestris pv. campestris) and three bacteria of food (Enterococcus faecalis, Escherichia coli and Staphylococcus aureus) with chromatographic method which determined the minimum concentration of plant extract which stopped the growth of microorganisms (Minimum Inhibitory Concentration – MIC). The results of this research showed that the aqueous and acetone extracts had the highest concentration of total phenolic compounds. The highest content of the total phenolic compounds was founded in plants Salvia fruticosa and Origanum dubium. Additionally most of the plant extracts Salvia fruticosa had the highest level of derivatives ydroxykinammomikou acid and total flavonoids but using only polar solvents. Ideal solvent for receipt the total phenolic compounds was proved the water. Extracts of Salvia fruticosa and Origanum dubium had the highest concentration of total phenolic compounds and flavonoids. The plants Origanum dubium and Sideritis spp. showed the highest level of antioxidant capacity. Also, the acetone extract of the plant Salvia fruticosa showed the strongest antimicrobial activity for both phytopathogenic bacteria (150 μg/ml) and for all bacteria food (80 - 120 μg/ml). Significant antimicrobial activity (150 μg/ml) was observed in extracts of oregano and thyme with solvent ethyl acetate to the bacterium Xanthomonas campestris pv. campestris. The aqueous and methanol extracts showed the weaker antimicrobial activity.
Keywords: Βioactivity; Pharmaceutical; Plants; Βιοδραστικότητα; Φαρμακευτική; Φυτά